THE SYNTHESIS OF SPIRITUAL COGNITIVE BEHAVIORAL APPROACH TO UNDERSTANDING AND MODIFYING HUMAN BEHAVIOR - Alfaiz, Alfaiz; Fauzi, Yasir Muharram; Yuzarion, Yuzarion; Yandri, Hengki; Nofrita, Nofrita; Murisal, Murisal; Hasneli, Hasneli; Rafiola, Ryan Hidayat; Sari, Azmatul Khairiyah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to describe how the spiritual cognitive behavioral approach to understanding and modifying human behavior, to establish a good personality as an agentic person in social life, explain a relationship between spiritual perspective, cognitive behavioral perspective, and agentic aspects in social system, and synthesize a spiritual cognitive behavior technique (SCoBeT) as an approach to shape a personality and human behavior. Data was obtained using the critical analysis systematic literature review (SLR) method and it was gathered that Tazkiyatun An Nafs as a spiritual perspective with the concept of Takhalli, Tahalli and Tajalli and cognitive behavioral with the Agentic Aspects such Intentionality, Forethought, Self Reactiveness, Self Reflectiveness this aspects was extracted to be a new technique in order to shape a human personality and human behavior such emotional impuls, cognitive and behaving. The result of this study shows that spiritual and cognitive behavioral has a connection in conceptual and implementation perspective ways in theoretically and practically, and also has a relationship with shaping personality tendency and behavior in considering an action in social life. Moreover, in response to contemporary issues, spiritual cognitive behavior technique as an approach is synthesized and developed as a counseling technique in education and career manner.